ANALYSIS OF LINES FORMATION PRODUCED BY ELECTROHYDRODYNAMIC JET PRINTING FOR TERAHERTZ (THZ) METAMATERIALS FABRICATION - Tenggara, Ayodya Pradhipta; Yudistira, Hadi Teguh; Mtei, Brian Godwin; Byun, Doyoung (Universitas Mataram, 2025)
Electrohydrodynamic (EHD) jet printing has revolutionized semiconductor manufacturing technologies to fabricate high resolution materials pattens (metal, dielectric, or semiconductors) in small size. This technology can reduce excessive materials usage in conventional semiconductor lithographic technologies, such as photolithography or electron beam lithography, so that it can be categorized as a green manufacturing technology. EHD jet printing has a capability to fabricate resonant terahertz metamaterial. Resonant terahertz metamaterial contains metal structures in micrometer sizes patterned on dielectric substrate. The metal structures are arranged periodically to generate resonances in specific frequencies, which are beneficial for several applications, such as biosensing, chemical sensing, and terahertz optical modulators for future communication devices. To make a high resolution and repeatable structures, EHD jet printing faces two main problems, i.e. the drop coalescence problem and the charge problem. The charging problem can be solved by removal of substrate charges using ionizer. However, the drop coalescence problem is a type of complex problem that needs to be studied and optimized systematically to produce repeatable and reliable terahertz resonant metamaterial structures, which is electric split ring resonator (ESRR). The objective of this research is to investigate to the formation stability of dots and lines produced by the EHD jet printing. We used EHD jet printing through the Drop on Demand (DoD) method to deposit droplets from metal nanoparticle ink with various volumes on dielectric substrates with different thickness. Several parameters were investigated, i.e. the droplet volume, the droplet spacing, and the substrate thickness. The results showed that by increasing the deposited droplet volumes and decreasing the substrate thickness, the stability of line formation was improved. Moreover, the stability analysis of line formation revealed that by using the bigger volume, the minimum printing speed to make uniform line was decreased, because the bigger droplet volume gave smaller contact angle. The results also showed that the uniformity of metamaterials patterns could be improved by using the smaller width.